Strategic Communication Approaches for Optimizing Zakat in The Digital Era - Hakim Kusuma, Andi; Bahruna, Setiawan (Jurnal Manajemen, 2026)
The digital transformation of Islamic finance has reconfigured the mechanisms of Zakat collection, management, and distribution. Although Islamic fintech offers technological innovations with significant potential to optimize global Zakat resources, estimated to exceed USD 600 billion annually, effectiveness remains highly dependent on strategic communication that fosters transparency, trust, and socio-religious legitimacy. This study adopts a mixed-methods design combining systematic literature review, comparative case analysis of digital Zakat platforms, and conceptual framework development. Qualitative thematic analysis was applied to identify dominant communication patterns and contextual determinants shaping user adoption and engagement within digital religious philanthropy ecosystems. Three dominant communication models were identified: trust-centric, community-driven, and personalized communication models. Each model corresponds to specific contextual variables, including institutional credibility, social capital structures, and user technological literacy. Communication effectiveness was further strengthened through alignment with technological affordances, particularly blockchain-based transparency and AI-enabled personalization. Cultural adaptation, including linguistic localization, Islamic aesthetic representation, and gender-sensitive messaging, emerged as a critical factor in enhancing platform legitimacy and user participation. The study formulates a multi-layered strategic communication framework for digital Zakat platforms, offering actionable insights for Zakat institutions, fintech developers, and policymakers, while contributing broader theoretical implications for the digitalization of religious obligations within contemporary digital ecosystems.